Peritoneal dermoid cyst, rare location with no other primary focus: a rare case report - Sai Sampath Kumar Vasantham; Jameel Akhter (International Surgery Journal, 2023)
Growth of dermoid cyst on parietal peritoneum without any prior history of ovarian dermoid cyst is considered a rare condition. The presentation of peritoneal dermoid cyst is vague and depends on the location of the cyst. We report a case of a 28-year-old young female who presented at our outpatient department with vague right upper quadrant pain and no other complaints, but upon examination a swelling was felt on the right upper quadrant, she was investigated radiologically, which reported as a peritoneal cyst, she was taken up for surgery. The cyst was excised and confirmed histopathologically as a dermoid cyst. Clinical progress was uneventful and postoperative recovery was excellent.